International currency, credit and financial relations - Корнелюк, Ольга Антонівна; Korneliuk, Olha A. (Lesya Ukrainka Eastern European National University, 2019)
The educational discipline is intended to acquaint students with the the essence of monetary and financial relations, forms and instruments of their implementation, elements of the international finance system; characteristics of the world financial market and its segments; methods of using the main financial instruments; determining the role of Ukraine in international monetary and financial relations.